An approach of preserving a mandibular primary second molar by a hemisection procedure: A case report with 36-month follow up - Louay Hanafi (Heliyon, 2022)
Primary teeth play a crucial role in functional, aesthetic and speech tasks. They are also responsible for maintaining the jaw space for successor permanent teeth. Thus, dentists should understand that extraction might be the easiest decision but not always the correct one, especially, in the case of multiple loss of primary molars. On the other hand, endodontic treatments should be accurately diagnosed - necrotic and irreversibly inflamed teeth - and performed with suitable dental tools and materials. Then it is important to provide a good sealing with a suitable final restoration. This case report discusses an approach for preserving a mandibular primary second molar which had a radiographic lesion in the mesial root and the furcation area with multiple loss of primary molars (before eruption of first permanent molar). This treatment was done by performing a root canal treatment (pulpectomy) just for the distal root and a hemisection procedure by extracting the mesial root, followed by applying SSC crown and space maintainer (band and loop). To conclude, this type of treatment should be temporary until the eruption of the first permanent molar and then changed to be a lingual arch appliance. Moreover, hemisection was a suitable alternative approach to extraction over 36 months of following up.